Strategic incentives in intermediary markets: Field-experimental evidence - Max Thon; Oliver Gürtler; Matthias Heinz; Kai Schäfer; Dirk Sliwka (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
We investigate how to strategically motivate sales agents in intermediary markets. In collaboration with a large travel company, we run a field experiment with more than 1, 200 independently owned intermediaries that sell our study firm's own products as well as products from competitors to end customers. The intermediaries employ sales agents responsible for customer interaction. We compare the impact of different forms of monetary incentives with non-monetary incentives provided through direct support to reduce the sales agents' effort costs. We develop a conceptual formal model hypothesizing that incentives for intermediaries (i) generally increase sales, and are more effective when targeting (ii) sales agents rather than owners of the intermediaries, (iii) intermediaries with weaker monetary incentives prior to the intervention, and (iv) products where the firm has no competitive advantage. We find that providing sales-agent support increases sales, while higher commission payments to the agencies' owners has no discernible effects. Directly incentivizing sales agents through vouchers raises sales for agencies with low prior commission rates. The incentive effects are driven by products where the firm has a weaker market position, while they have no discernible effects on product sales where the firm has a strong competitive advantage. We analyze underlying mechanisms using surveys and further administrative data.
Keywords: C93; D23; L21; M52; 330; Incentives; intermediaries; competitive advantage; strategy; productivity; field experiment